POPE, PROVINCE, AND POWER: The authority of the Nidaros metropolitan see, c. 1240–1265. Issue 3 (27th May 2017) - Øvergård Beistad, Heidi Anett
Abstract : The Nidaros province, founded in 1152–1153 with Nidaros/Trondheim in Norway as its metropolitan see, was a wide-spanning unit encompassing the episcopal sees in Norway, Iceland, Greenland, The Faeroes, Orkney, and The Isle of Man. This article discusses a period in the history of the province which has attracted little scholarly attention to date. The point of departure is the archbishop's apparent disappearance from the Icelandic scene in the 1240s, and the author addresses the question of ecclesiastical integration by examining the Nidaros metropolitan's authority in the mid-13th century. The subject is approached from three perspectives: the archbishop's relationship with the pope; the struggle for power between the archbishop and the Norwegian king; and the archbishop's executive authority within his province, exemplified by the Icelandic Church. The article reveals that in the mid-13th century the archbishop was facing several challenges to his authority. The analysis also provides compelling insights into the dynamics at work within the wider context of the high medieval Church.